2015
DOI: 10.1075/pbns.255.09pin
|View full text |Cite
|
Sign up to set email alerts
|

Responses to indirect complaints as restricted activities in Therapeutic Community meetings

Abstract: In this chapter I investigate how the staff members of a mental health Therapeutic Community in Italy avoid displays of affiliation in response to residents' indirect (or third party) complaints. I show how this restriction can be embodied in different practices: ignoring a resident's turn carrying a possible complaint, avoiding attending the complaint-components of a resident's turn, and disaffiliating with a resident's complaint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…164–165). This, though, presents challenges for analysts; and the issue of identifying complaints as complaints when they are implicitly designed, when there is no explicit orientation by participants to the ‘moral work’ (Drew, 1998, p. 302) being done in the detailing of some matter, has been widely discussed in the research literature (Drew, 1998; Edwards, 2005; Pino, 2015; Schegloff, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…164–165). This, though, presents challenges for analysts; and the issue of identifying complaints as complaints when they are implicitly designed, when there is no explicit orientation by participants to the ‘moral work’ (Drew, 1998, p. 302) being done in the detailing of some matter, has been widely discussed in the research literature (Drew, 1998; Edwards, 2005; Pino, 2015; Schegloff, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, it is clear that successive interactions within largely the same participation framework are likely to be at issue (e.g. Heinemann, 2009; Laforest, 2009; Pino, 2015). In none of these studies, though, is successivity the focus of the analysis.…”
Section: Complaints and Later‐life Relationsmentioning
confidence: 96%
See 1 more Smart Citation
“…difficulties, but such behaviour may simply be a more practical and thus potentially efficient thing to do. In this respect, Pino (2015) demonstrated that staff members of a mental health institution disattend to patients' complaints by letting them pass and continue with the ongoing activity precisely for this reason.…”
Section: Types Of Impolitenessmentioning
confidence: 99%
“…Complaints about service provision are ubiquitous, whether they are manifested directly to the service provider or to a third party. It is therefore not surprising that research on complaints in institutional settings has attracted much attention and supplied the knowledge on how the participants carry out complaint sequences and the strategies they use in an attempt to achieve their interactional goal (Márquez Reiter, 2005Heinemann, 2009;Monzoni, 2008Monzoni, , 2009Ruusuvuori & Lindfors, 2009;Pino, 2015). Broadly speaking, to complain is to report a particular problem that had already occurred and in doing so express a sense of dissatisfaction or unfairness.…”
Section: Previous Studies On Complaints In Institutional Settingsmentioning
confidence: 99%